Impact of nonalcoholic fatty liver disease on the functional cure of nucleos(t)ide analogues-treated chronic hepatitis B patients add-on pegylated interferon therapy: a retrospective study - Li, Huili; Li, Ling; Zhao, Yiru; Yang, Guangde; Wang, Xia; Fu, Juanjuan; Li, Li; Pan, Xiucheng (PeerJ, 2025)
Background This study aimed to determine whether nonalcoholic fatty liver disease (NAFLD) influences the functional cure of nucleos(t)ide analogues (NAs)-treated chronic hepatitis B (CHB) patients in combination with pegylated interferon (PEG-IFN) therapy. Methods A retrospective analysis was conducted on CHB patients treated with nucleos(t)ide analogues (NAs) who received PEG-IFN combination therapy at a single center. Patients were stratified into a CHB group and a CHB-NAFLD group based on the presence of fatty liver comorbidity. The primary endpoint was the difference in hepatitis B virus surface antigen (HBsAg) seroclearance rates between the two groups, and the secondary endpoint was the differences in biochemical parameters and adverse events. Results A total of 158 NAs-treated CHB patients were enrolled, comprising 91 CHB -only patients and 67 CHB-NAFLD patients. After 48 weeks of PEG-IFN therapy, 20.9% of patients achieved HBsAg seroclearance. Before and after propensity score matching (PSM), differences in cumulative HBsAg seroclearance probability between groups were non-significant (25.3% vs. 14.9% , P = 0.121; 32.4% vs. 13.5%, P = 0.063). Similarly, cumulative hepatitis B e antigen (HBeAg) seroconversion incidence showed no intergroup differences before and after PSM (P = 0.618 and P = 0.954, respectively). Logistic regression analysis indicated that baseline HBeAg status was independently associated with HBsAg seroclearance. Further analysis confirmed that NAFLD did not significantly affect HBsAg loss, regardless of HBeAg status, both before and after PSM (P > 0.05). Moreover, the NAFLD group exhibited higher rates of abnormal alanine aminotransferase (ALT) at weeks 24 and 48 versus the CHB-only group (31.9% vs. 12.3%, P = 0.009; 70.8% vs. 47.4%, P = 0.007). However, ALT normalization rates 24 weeks post-treatment showed no significant difference (88.9% vs. 77.2%, P = 0.074). Conclusion NAFLD does not affect the achievement of functional cure with PEG-IFN therapy in NAs-treated chronic hepatitis B patients. However, CHB patients with NAFLD show a reduced likelihood of ALT normalization during treatment.
Keywords: Chronic hepatitis B; NAFLD; PEG-IFN; Nucleos(t)ide analogues; Functional cure